Cone Beam Computed Tomography Evaluation of the Periapical Status of Nonvital Tooth with Open Apex Obturated with Mineral Trioxide Aggregate: A Case Report - Vijay Shekhar; K. Shashikala (Case Reports in Dentistry)
Management of a tooth with open apex is a challenge to the dental practitioners. Evaluation of the periapical healing is required in such cases by radiographic techniques. The objective of this paper was to assess the healing of a periapical lesion in a non-vital tooth with open apex treated with mineral trioxide aggregate (MTA) obturation using cone beam computed tomography (CBCT). The endodontic treatment of a fractured non-vital discolored maxillary left lateral incisor with an open apex was done with MTA obturation. The clinical and radiographic followup done regularly showed that the tooth was clinically asymptomatic and that the size of the periapical lesion observed by intraoral periapical (IOPA) radiographs and CBCT was decreased remarkably after two years. CBCT and IOPA radiographs were found to be useful radiographic tools to assess the healing of a large periapical lesion in a non-vital tooth with open apex managed by MTA obturation.